2022
DOI: 10.1002/pcn5.58
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective chart review‐based assessment scale for adverse childhood events and experiences

Abstract: Aim: Adverse childhood experiences (ACEs) are highly prevalent in the general population, and their lifelong impact on physical and mental health is profound. In assessing ACEs, it is vital to consider the pathways and modalities by which an individual internalizes events as an adverse experience and its effects on their biological, psychological, and social function. However, conventional assessments of ACEs are inadequate in that they do not comprehensively assess the source of the adverse event and the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Focusing on the ACE contents, the prevalence of vertical sources was high. Comparing the percentages between our study and that of inpatients [5], psychological separation (28% vs 12%), psychological invasion (13% vs 5%), and physical witness (13% vs 3%) were more than twice as high. Many service users have lived with their families after adulthood, and it is likely that at the time of service initiation, they still have di culties in family relationships.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…Focusing on the ACE contents, the prevalence of vertical sources was high. Comparing the percentages between our study and that of inpatients [5], psychological separation (28% vs 12%), psychological invasion (13% vs 5%), and physical witness (13% vs 3%) were more than twice as high. Many service users have lived with their families after adulthood, and it is likely that at the time of service initiation, they still have di culties in family relationships.…”
Section: Discussionmentioning
confidence: 47%
“…A previous national-level study in Japan reported that 32% of the general adult population had at least one ACE [17]. Another national study, which assessed ACEs among patients who participated in a four-day inpatient program for psychiatric diagnosis using the RC-ACEE scale, reported that 46% had at least one ACE and 18% had more than two ACEs [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations